Screening for atrial fibrillation - Zhenisgul Tlegenova; Gulmira Kudaiberdieva; Bekbolat Zholdin; Ayan Abdrakhmanov (National Scientific Medical Center, 2018)
Atrial fibrillation is the most common arrhythmia that physicians face in their clinical practice. Atrial fibrillation is associated with a higher risk of thromboembolic events, all-cause mortality, frequent hospitalizations, decreased quality of life. Early detection of atrial fibrillation is important for optimal management and improvement the prognosis of atrial fibrillation patients. Evidence on new methods of atrial fibrillation screening discussed in this review, allows considering them more accurate than simple pulse palpation.